Impact of the COVID-19 Pandemic on the Distribution of Viral Pathogens Involved in Febrile Seizures - Eda Kepenekli; Gülser Esen Besli; Mahmut Firat Halici; Aytac Goktug; Gizem Dikencik-cuceloglu; Emel Ekşi Alp (Experimed)
Objective: To evaluate the impact of the COVID-19 pandemic on the distribution of viral pathogens responsible for febrile seizures (FS) in children.Materials and Methods: This multicenter study reviewed cases diagnosed as compatible with FS between March 2018 and March 2022. Patients who underwent viral testing were included. Demographic and clinical data were reviewed from the system files.Results: Laboratory tests targeting viral etiology were performed in 114 of 1683 patients with FS. The viral etiology of FS was consistent before and during the pandemic. The findings demonstrated a statistically significant increase in the number of patients who reported their first FS during the pandemic (81.3%) as opposed to before (63.6%) (p=0.041). There were no significant differences in viral test positivity rates before and during the pandemic (p=0.817). While influenza virus was mostly isolated in the pre-pandemic period, influenza and SARS-CoV-2 were almost equally isolated in the post-pandemic period.Conclusion: Febrile seizures are usually benign, with no adverse events. However, this situation may be stressful for families, but identifying the cause can provide relief. The development of rapid diagnostic tests that simultaneously screen for both SARS-CoV-2 and influenza viruses could be valuable for efficient patient follow-up and treatment.